Now or never : thirty-one on the run [large type] - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel, 2024)
"Stephanie Plum's life is ready to explode: she said yes to Morelli and Ranger. Now she has two fiancés and no plan. Stalling for time, Stephanie buries herself in her work as a bounty hunter, tracking down fugitives, and she has to use every trick tin the book to reel them in. But she can't decide what to do about Ranger and Morelli--and the secret she's keeping from them is the biggest bombshell of all. Now or never, she's got to make the decision of a lifetime" --